Environmental Risks Associated with the Exploitation of Oil Fields - Bagirov, A.A.; Shirinov, M.M.; Samedov, V.N.; Bogopolsky, V.O. (Herald of Azerbaijan Engineering Academy, 2023)
The article is devoted to the study of the causes of environmental risks in the oil and gas industry in the context of environmental protection. Environmental risk - the risk associated with the normal operation of the industry; operational, chemical, industrial wastewater, emergency discharges and discharges. It mainly provides information on the risks that may arise when drilling and operating oil and gas wells in offshore conditions. The concept of environmental risk is accepted not only as a criterion of environmental cleanliness, but also as a key indicator of human health.